Reflexões preliminares a propósito de formas de organização de espaço e de técnicas de construção em sítios pré-históricos recentes (Calcolítico/I. Bronze) do tipo de Castelo Velho e de Castanheiro do Vento (Vila Nova de Foz Côa) - semelhanças e diferenças em relação às construções megalíticas e afins - Jorge, Susana Oliveira; Jorge, Vitor Oliveira; Cardoso, João Muralha; Pereira, Leonor Sousa; Coixão, António Sá (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This paper is based in a experience of field work carried out in the prehistoric sites of Castelo Velho, Freixo de Numão (direction: SOJ, since 1989) and Castanheiro do Vento, Horta do Douro (direction: VOJ, JMC, LSP, ASC and, in the last years, also Ana Vale - since 1998). Both sites are located in the territory of the municipality of Vila Nova de Foz Côa, situated in the Portuguese High Douro). The study is focused in building techniques and the spatial organization of these huge architectonic displays. A very general comparison is made with the so-called Neolithic passage graves (Middle/Late Neolithic). The authors try to underlie the main contrasts that seem to exist between these “burial” monuments and the walled “precincts” of Copper and Bronze Ages. Those conclusions are presented as very contingent and schematic, and as being mainly applied to the archaeological reality of northern Portugal.